Influence of cisplatinum and 5-fluorouracil on the oral mucosa - Zöller, Joachim E.; Flentje, Michael; Born, Ivan Antonio; Osswald, Hans (European journal of cancer. B, Oral oncology, 1994)
In a prospective study we examined the effect of preoperative chemotherapy with cisplatinum and 5-fluorouracil (5FU) in 40 patients with a carcinoma of the oral cavity. Histopathological grading, cell kinetic and immuno-histochemical parameters of the mucosa were determined at two different locations. Prior to therapy histological dysplasias “close” to the tumour were observed in the mucosa of 75% of the patients. Dysplastic changes of the mucosa “far” from the tumour were also found in more than one third of the patients. Our results show that more advanced dysplasias improve under the influence of preoperative systemic chemotherapy only temporarily. Moreover, new dysplasias which appeared during chemotherapy and persisted after its termination are probably induced.
Gesehen am 06.02.2025
Elektronische Reproduktion der Druck-Ausgabe 15. April 2004